Answer:
x -6y = -15
Explanation:
There are several ways we can get from the given points to a standard-form equation for the line through them. One way is to equate the slope from a general point (x, y) to point C with that of the slope from point D to point C.
__
The slope of a line between two points is ...
m = (y2 -y1)/(x2 -x1)
From (x, y) to C:
m = (y -3)/(x -3)
From D to C:
m = (2 -3)/(-3 -3) = -1/-6 = 1/6
__
Equating these slopes, we have ...
(y -3)/(x -3) = 1/6
6(y -3) = (x -3) . . . . . multiply by 6(x -3)
6y -18 = x -3 . . . . . . eliminate parentheses
x -6y = -15 . . . . . . . add 3-6y
_____
Additional comment
The standard form equation of a line is ...
ax +by = c
where a > 0, and 'a', 'b', 'c' are mutually prime integers.
Usually, we like to have the variables in lexicographical order, so the first term will be the x-term, and its coefficient will be positive.